Profile and outcome of post stroke patients managed at selected public primary care health centres in Peninsular Malaysia: A retrospective observational study. Issue 1 (December 2018) - Abdul Aziz, Aznida; Ali, Mohd; Yusof, Mohammad; Che' Man, Zuraidah; Sulong, Saperi; Aljunid, Syed
Abstract Data on post stroke outcomes in developing countries are scarce due to uncoordinated healthcare delivery systems. In Malaysia, the national stroke clinical practice guideline does not address transfer of care and longer term post stroke care beyond tertiary care. Hence, post stroke care delivery may be delivered at either tertiary or primary care facilities. This study aimed at describing patients' characteristics and outcomes of post stroke care delivered by the primary care teams at public primary care healthcentres across Peninsular Malaysia. Multi staged sampling was done to select public primary care health centres to recruit post stroke patients. At each health centre, convenience sampling was done to recruit adult patients (≥18 years) who received post stroke care between July-December 2012. Baseline measurements were recorded at recruitment and retrospective medical record review was done simultaneously, for details on medical and / or rehabilitation treatment at health centre. Changes in the measurements for post stroke care were compared using paired t-tests and Wilcoxon Rank test where appropriate. Total of 151 patients were recruited from ten public primary care healthcentres. The mean age at stroke presentation was 55.8 ± 9.8 years. Median duration of follow up was 2.3 (IQR 5.1) years. Majority co-resided with a relative (80.8%), and a family member was primary caregiver (75.%). Eleven percent were current smokers. Almost 71.0% of patients achieved BP ≤ 140/90 mmHg. Only 68.9% of the patients had been referred for neurorehabilitation. Percentage of recorded data was highest for blood pressure (88.1%) while lowest was HbA1c (43.0%). For clinical outcomes, systolic and diastolic blood pressure, triglyceride level and calculated GFR (eGFR) showed statistically significant changes during follow up (p < 0.05). Post stroke care at public primary care healthcentres showed benefits in stroke risk factors control (i.e. hypertension and dyslipidaemia) but deterioration in renal function. A more structured coordination is needed to optimise post stroke care beyond acute phase management for patients who reside at home in the community.